Investigation of Oiling‐Out Phenomenon of Small Organic Molecules in Crystallization Processes: A Review. Issue 26 (9th July 2020) - Meng, Zichao; Huang, Yan; Cheng, Shuo; Wang, Jingtao
Abstract: Oiling‐out phenomenon occurs in many crystallization processes and might cause processing problems especially in the drug crystallization. This paper discusses the mechanism of oiling‐out processes from the thermodynamics, crystallization kinetics, molecular simulation and other important factors. This review clarifies the intrinsic relationship between oiling‐out and crystal nucleation and growth on the basis of the relevant theories, and tries to explore possible strategies to the problems caused by oiling‐out. Three strategies, optimization of initial conditions, seeding and ultrasonic irradiation, have been developed to control and avoid oiling‐out. Finally, several suggestions for the future research of oiling‐out including the study in molecular level (Van deer Waals forces, H‐bonding and dipole moments et al.), simulation and microfluidics are presented. This review will be helpful to those readers whose researches involve the liquid‐liquid phase separation and crystallization. Abstract : This article comprehensively discusses the phenomenon of oiling‐out during the crystallization of organic small molecules, and systematically summarizes the knowledge points (development, tools, causes and possible solutions) involved in the oiling‐out behavior. This review will be helpful to those readers whose researches involve the oiling‐out and crystallization.